THE ROLE OF PHYSICAL EDUCATION IN THE UNIVERSAL AND PROFESSIONAL TRAINING OF CADETS - Kdirovа Mukhabbat Allaniyazovna (PEDAGOGS, 2024)
Annotation: In our Country, serious attention is paid to the issue of expanding the worldview of young people, the formation of a spiritual and spiritual image. By the perfect generation we are both spiritually and physically healthy humannwhich we bring before us. Therefore, along with the formation of physical perfection in young people, Wide Opportunities are being created for the development of moral qualities in them, the formation of aesthetic duos. In recent years, many works have been carried out to strengthen the legislative framework for the development of physical education and sports.